Edith Stein Brings the Memory of the Shoah into the Heart of the Church - Deselaers, Manfred (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2016)
In the year 2012 we commemorated the 70th anniversary of the death of Edith Stein in Auschwitz. Together with the Polish Council of Christians and Jews, a Way of Prayer took place along the railway ramp which leads to the crematoria. Bishops of all the dioceses where she once had lived celebrated Eucharist next to the crematoria. In January 1933, when Hitler came to power, Edith Stein wrote a prophetic letter to Pope Pius XI about the relationship of the Church to the Jews. In October 1933, she entered the Carmel where she chose the name of Teresa Blessed by the Cross. For her, all her life in the Carmel was a way of solidarity with her Jewish people. In Auschwitz she shared the fate of her people who were destroyed in the Shoah. She compels us as Christians to take the Shoah seriously.